A retrospective evaluation of the clinical monitoring period prior to referral for glaucoma surgery with the emphasis on visual field test results - Jesper L. Hougaard; Boel Bengtsson (BMC Ophthalmology)
Abstract Purpose To survey the monitoring of patients who underwent glaucoma surgery with the purpose of identifying routines possibly delaying the referral process. Methods We conducted an observational retrospective study of the 2-year period prior to referral of a cohort of patients who underwent trabeculectomy or Xen® Gel Stent implantation at Skåne University Hospital (SUS), Sweden. Data were retrieved from medical records; variables of particular interest were related to intraocular pressure (IOP) measurements and visual field (VF) tests. Results Out of 330 patients who underwent surgery, 139 were included. There were 20 referring clinics in total; SUS and two clinics in private practice accounted for 55.4% of all referrals. Prior to referral, the most common number of VF tests per patient was three, and 43.2% (60/139) had ≥ 10 IOP measurements. According to the last VF test, 51.1% had lost > 50% of a full VF. During the 2-year period, 21.9% (28/128 with ≥ 2 VF tests) progressed from ≥ 50% to < 50% remaining of a full VF. The median rate of progression of VF damage was -6.8%/year in the 107 patients who had ≥ 3 VFs, and 67.3% (72/107) were projected, by extrapolation of the linear trend, to lose > 50% of a full VF if the referral had been postponed for 2 years. At the time of the last IOP measurement prior to referral, 84% (117/139) of the patients were on ≥ 3 IOP-lowering agents, and the IOP ranged from 11–45 mmHg, with a median of 20 mmHg. Conclusion In general, in the 2-year period prior to referral for surgery, the number of IOP measurements was high, and the number of VF examinations seemed acceptable in most cases. Nevertheless, > 50% had advanced to severe VF loss and fast progression prior to referral. The IOP level is a known risk factor for disease progression that should be monitored at least by VF tests, but the frequent IOP measurements observed in our study, probably due to treatment changes, may have delayed the time to referral.